PLan de mejoramineto de las ferias solidarias, desarrolladas en el gobierno autónomo descentralizado municipal de San Pedro de Pimampiro, Tierra del Sol - Alarcón Guerra, Alberto Jonatan (2014)
This research aims to develop a plan for improving Pimampiro´s solidarity fairs, to strengthen them; under these fairs help promote the people's economy and food sovereignty. The theoretical support of the research topic considers important aspects, such as management and process management, social, popular and solidarity economy, national development plan and good living, food sovereignty, supply chains, charity baskets, bioferias, rural development sustainable, local community involvement, participatory plans and strategic plans. In the second chapter a comprehensive organizational analysis is done of the ASOCIACIÓN DE DESARROLLO SOCIAL E INTEGRAL TIERRA DEL SOL DE PIMAMPIRO, where the environment is evaluated and must consider all external and internal agents that may affect the business; well as competitors and consumers. In addition to gathering information a field research was done, where you can identify the main problems for the proper development of the Fair is done. The information processed by the application of supply and demand surveys with their analysis and interpretation, coupled with the detection of the problems encountered in the show, are the backbone of development in chapter three, where the necessary strategies are determined. In chapter four, the proposed strategies are developed and therefore the activities to be implemented, prior use of Pareto; at this point the required resources are described. Finally, conclusions and recommendations are presented.